The norton introduction to literature (W.W. Norton, 2002)
A balanced selection of classic and contemporary works by prominent and less-well-known writers. From Joyce, Hemingway, O'Connor, Auden, Stevens, Dickinson, Faulkner, Hawthorne, and Whitman, to Sharon Olds, Nicholson Baker, Carolyn Forché, Paul Ruffin, Salman Rushdie, Agha Shahid Ali, Eamon Grennan, Linda Pastan, Li-Young Lee, Jimmy Santiago Baca, Simon Ortiz, Seamus Heaney, Karen Volkman, and David Ives.